Genetic and hormonal mechanisms underlying sex-specific immune responses in tuberculosis. Issue 8 (August 2022) - Gupta, Manish; Srikrishna, Geetha; Klein, Sabra L.; Bishai, William R.
Abstract : Tuberculosis (TB), the world's deadliest bacterial infection, afflicts more human males than females, with a male/female (M/F) ratio of 1.7. Sex disparities in TB prevalence, pathophysiology, and clinical manifestations are widely reported, but the underlying biological mechanisms remain largely undefined. This review assesses epidemiological data on sex disparity in TB, as well as possible underlying hormonal and genetic mechanisms that might differentially modulate innate and adaptive immune responses in males and females, leading to sex differences in disease susceptibility. We consider whether this sex disparity can be extended to the efficacy of vaccines and discuss novel animal models which may offer mechanistic insights. A better understanding of the biological factors underpinning sex-related immune responses in TB may enable sex-specific personalized therapies for TB. Significance: Tuberculosis (TB) continues to remain one of the world's most important medical challenges with a significant male bias. Elucidating the underlying mechanisms that mediate differences in immune responses to Mycobacterium tuberculosis in males and females will not only enlighten our understanding of TB pathogenesis but also aid in developing novel sex-specific vaccines and therapies. Highlights: Human adult males are 1.7-fold more likely than females to develop active tuberculosis (TB) disease. Recent studies indicate that reporting biases and differential healthcare access do not fully explain the higher TB incidence in males worldwide. Sex steroid hormones, sex chromosome-encoded genes, and miRNAs differentially modulate innate and adaptive immune responses to TB in males and females, both in humans and in animal models of TB. Research addressing the biological bases for the male bias is likely to provide novel insights into the pathogenesis of active TB disease and latent TB infection. Understanding the immunological basis for the male bias might enable the development of precision medicine interventions for TB, including host-directed therapies that are sex-specific. Dissecting the molecular and immunological mechanisms of the male bias in TB will benefit from improved animal models and sex-linked biomarkers that can predict the risk of developing active disease.